2022
DOI: 10.13057/biodiv/d230606
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Salmonella species from chicken meat sold at Surabaya Traditional Markets, Indonesia

Abstract: Abstract. Fanissa F, Effendi MH, Tyasningsih W, Ugbo EN. 2022. Multidrug-resistant Salmonella species from chicken meat sold at Surabaya Traditional Markets, Indonesia. Biodiversitas 23: 2823-2829. Salmonella species is one of the major infectious pathogens associated with poultry birds, which also has an impact on public health. Antimicrobials are used as growth promoters or treatment of diseases thus; this encourages the persistent spread of antimicrobial resistance (AMR). This study aimed to identify multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Studies from developing Asian countries reported a prevalence of 46.3% in central Vietnam (Barua et al 2012) and 42% and 18% in Bangladesh, respectively (Lettini et al 2016;Sarker et al 2021). Fanissa et al (2022) reported a low prevalence of Salmonella species in Surabaya, Indonesia, with a frequency of 11.3%. Other researchers have observed a similar prevalence of Salmonella species; poultry samples 23.53% (Al-Mamun et al 2017); poultry production 37.9% (Mahmud et al 2011), chickens 11.54% (Abd El-Aziz et al 2021) and broiler farms 31.25% (Mridha et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies from developing Asian countries reported a prevalence of 46.3% in central Vietnam (Barua et al 2012) and 42% and 18% in Bangladesh, respectively (Lettini et al 2016;Sarker et al 2021). Fanissa et al (2022) reported a low prevalence of Salmonella species in Surabaya, Indonesia, with a frequency of 11.3%. Other researchers have observed a similar prevalence of Salmonella species; poultry samples 23.53% (Al-Mamun et al 2017); poultry production 37.9% (Mahmud et al 2011), chickens 11.54% (Abd El-Aziz et al 2021) and broiler farms 31.25% (Mridha et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The multidrug resistance Salmonella strain isolated in this study showed 75% to 100% susceptibility to fluoroquinolones (ciprofloxacin), carbapenem (imipenem), aminoglycosides (gentamicin) in accordance with the report of Wibisono et al 2021 The multidrug resistance Salmonella isolates in this research were mostly resistant to penicillins (ampicillin), tetracycline, fluoroquinolones (ofloxacin), sulfonamides (sulphamethoxazole/trimethoprim) and nitrofurans (nitrofurantoin) with their resistant ranging from 50% to 100%. The resistant patterns includes; AMP-FT-OFX-SXT-TE; TE-AMP-SXT-FT; AMP-IPM-FT-SXT-TE; AMP-OFX-CTX-FT-SXT-TE; AMP-SXT-CTX-TE; AMP-SXT-TE-CTX-FT; AMP-FT-SXT-TE-C; AMP-CIP-IPM-OFX-TE-CTX; AMP-CTX-OFX-SXT-TE; AMP-FT-OFX-TE-CTX-C. A study conducted in Surabaya, Indonesia, has reported a similar multidrug resistance pattern against Salmonella strains isolated from poultry across three antimicrobial classes such as TE-CIP-SXT, TE-CHL-SXT, and four antimicrobial classes ATM-TE-CIP-CHL -SXT, TE-CIP-CHL-SXT (Fanissa et al 2022). Another study reported the presence of multidrug resistance of the Salmonella strain with resistance patterns as AMP-SXT-CTX-C-TE; AMP-CTX-C-LEV-STX; C-TE-STX and AMP-C-TE (Nguyen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By measuring the diameter of the inhibition zone formed around the antibiotic disc with a vernier caliper, the disc diffusion method was used to read the antibiotic sensitivity test results (Fanissa et al 2022). The Clinical and Laboratory Standards Institute (CLSI) 2020 is used to analyze measurements of the bacterial inhibition zone.…”
Section: Antibiotic Sensitivity Testmentioning
confidence: 99%